2015
DOI: 10.1038/ncomms7557
|View full text |Cite|
|
Sign up to set email alerts
|

Tonic endocannabinoid-mediated modulation of GABA release is independent of the CB1 content of axon terminals

Abstract: The release of GABA from cholecystokinin-containing interneurons is modulated by type-1 cannabinoid receptors (CB1). Here we tested the hypothesis that the strength of CB1-mediated modulation of GABA release is related to the CB1 content of axon terminals. Basket cell boutons have on average 78% higher CB1 content than those of dendritic-layer-innervating (DLI) cells, a consequence of larger bouton surface and higher CB1 density. The CB1 antagonist AM251 caused a 54% increase in action potential-evoked [Ca2+] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 51 publications
1
32
0
1
Order By: Relevance
“…Interestingly, although the rise time of the events originating from the CCKBCs was significantly slower, the location of their synapses was not distinct from those of PVBCs. This data indicates that the difference in rise times might derive from the spatiotemporal profile of neurotransmitter release, as it was described in the hippocampus (Bucurenciu et al, 2008; Lenkey et al, 2015). The distinct release machinery might also be responsible for the observed differences in the latency of the responses.…”
Section: Discussionsupporting
confidence: 66%
“…Interestingly, although the rise time of the events originating from the CCKBCs was significantly slower, the location of their synapses was not distinct from those of PVBCs. This data indicates that the difference in rise times might derive from the spatiotemporal profile of neurotransmitter release, as it was described in the hippocampus (Bucurenciu et al, 2008; Lenkey et al, 2015). The distinct release machinery might also be responsible for the observed differences in the latency of the responses.…”
Section: Discussionsupporting
confidence: 66%
“…Lenkey et al . () have tested the hypothesis that the strength of CB 1 ‐mediated modulation of GABA release is related to the CB 1 content of axon terminals. Using the CB 1 antagonist AM251 they have shown that it caused an increase in action potential‐evoked in GABA axons.…”
Section: Cannabinoids and Gabamentioning
confidence: 99%
“…First we characterized the basic properties of inhibitory synaptic transmission between interneurons and their PC targets. We used a high KCl-based intrapipette solution for both pre-and postsynaptic cells (for details, see Methods) and used a CB 1 receptor antagonist AM251 to eliminate the potential tonic activation of CB 1 receptors at the output synapses of CCK+ cells, which might significantly alter the synaptic properties (Lenkey et al 2015). We calculated the basic properties of uIPSCs (10-90% rise time, decay time constant, latency, peak amplitude, synaptic potency and transmission probability) by averaging events evoked by single presynaptic spikes.…”
Section: The Type Of Interneuron Determines the Properties Of Uipscs mentioning
confidence: 99%
“…To pursue the molecular mechanism behind the differences of the release patterns is beyond the scope of the present study, although differences have been shown with respect to the Ca 2+ metabolism and release machinery for the two cell types (Hefft & Jonas, 2005;Lee et al 2009;Lenkey et al 2015).…”
Section: Differences In Transmission Properties (Unitary and Temporalmentioning
confidence: 99%